Application of nanomedicine in radiotherapy sensitization - Song, Xiaoyu; Sun, Zhenkun; Li, Li; Zhou, Lu; Yuan, Shuanghu (Frontiers in Oncology, 2023)
Radiotherapy is an essential component of cancer therapy. In current clinical cancer therapy, half of all cancer patients will be treated with radiotherapy either alone or combined with other types of therapies. As a powerful therapeutic approach, the therapeutic rationale of radiotherapy is that high-energy ionizing radiations interact with cancer cell, particularly deoxyribonucleic acid (DNA) to induce cancer cell death. However, toxicity to surrounding normal tissues often limits the maximum dose of irradiation that can be delivered to tumors. In addition, tumors include a high degree of heterogeneity in genotype, phenotype, and microenvironment, leading to variability in radiation sensitivity and response in different populations of tumor cells. Hence, new approaches for raising tumor responses to radiation need to be put on the agenda so that enhanced radiotherapy with low radiation doses can be achieved. With the rapid development in nanotechnology and nanomedicine, there are great interest in the use of nanomaterials as radiosensitizers to enhance radiation response and overcome radiation resistance. The objective of this article is to discuss the mechanisms and application of nano-radiosensitizers.